DEVELOPING A MODEL OF HOTS QUESTIONS FOR READING NARRATIVE TEXT - Evelyn Simanjuntak (Journal of English Educational Study (JEES), 2018)
In ESL classroom, teachers need qualified reading material together with some questions excercicesto fill students’ need to train their higher order thinking. This opinion is in accordance with Miskiah (2015,87). She said that the learning material plays a very important role in a learning process, it is the representation of teacher’s explanation in the classroom. On the other side, learning material is one of the learning aid to achieve the core competency. It also helps teachers in learning process, helps students to learn one component systematically so that the student may be able  to master a certain competency completely and integratedly. Moreover, learning material may be defined as series of facts, concept, foundation, procedures, and a devised generalisation specifically to make the learning process becomes easier (Abidin, 2012:33).This research analyses the effectiveness a product of HOTS questions for reading narrative text on IX grade students of SMPN 2 Jorong. the Procedure of instructionalmaterial development is aimed to make the material developed is suitable to the reader and the class condition.The research design applies 4D  (four D model) Research and Development. According to Thiagarajan, (1974:6-9), this has 4 steps that is : defining, design, development, and disseminating. By the research the writer tries to dig studets critical thinking and they can be the creative students in the future. Keywords: HOTS questions , reading, narrative text